HOW TO ENGAGE STUDENTS IN READING - Zulayho Mamasoliyeva Nizomiddin qizi (Web of Journals Publishing, 2024)
In this article, strategies of engaging students in reading are analyzed in learning new language. Also, this article shows that using interactive techniques more often can make a class more effective and give some useful recommendations and suggestions.
Keywords: engagement, strategy, reading, approach, students.